Pengaruh Kualitas Produk, Harga, Dan IklanTerhadap Keputusan Pembelian Sepeda Motor Yamaha(Setudi Pada Dealer Sumber Baru Rejeki Cabang Kartasura - Kurniawan, Aditya; , Ahmad Mardalis, SE.,MBA (2016)
This study aimed to analyze: 1) the influence of the quality of the product to the consumer decision in buying products Yamaha motorcycle. 2) the effect of price on consumer's decision to buy the product of Yamaha motorcycles. 3) the impact of advertising on consumer decision in buying a Yamaha motorcycle. 4) the impact of product quality, price, advertising simultaneously on consumer decision in buying productsYamahamotorcycle. The population in the study of customers of Yamaha motorcycles in deler New Source fortune. The samples used were 100 respondents. The method used in this research is by using multiple linear regression analysis to test the hypothesis that the t test and F test Before using multiple linear regression analysis, performed classical assumption befo. The results of this study are 1) Quality of products positive and significant impact on consumer purchasing decisions Dealer New Source Kartasura fortune. 2) Prices positive and significant impact on consumer purchasing decisions Dealer New Source Kartasura fortune. 3) Advertising positive and significant impact on consumer purchasing decisions Dealer New Source Kartasura fortune. 4) Quality of products, prices and advertising have a simultaneous effect on consumer purchasing decisions Dealer New Source Kartasura fortune.